Healthcare for truck drivers: Assessing accessibility and appropriateness of South African Roadside Wellness Centres. (March 2018) - Lalla-Edward, ST.; Matthew, P.; Hankins, CA.; Venter, WDF.; Gomez, GB.
Abstract: Background: Truck drivers occupy a pivotal role in the economies of southern Africa, due to limited rail, water and other forms of transport of goods. The occupational nature of truck driving limits access to healthcare. North Star Alliance (North Star) offers a tailored primary healthcare service for truck drivers along the sub-Saharan trucking corridor. Objectives: The overall objective of this study was to explore truck drivers' views regarding access to, and appropriateness of, selected South African North Star Roadside Wellness Centres (RWCs) coupled with understanding their health-seeking behaviour. Methods: We conducted semi-structured interviews with two groups of purposively-sampled truck drivers: 24 who accessed North Star RWCs and 22 who knew about the centres but did not use them. The interviews explored access, health-seeking behaviour, and healthcare experiences. Additional information on risk perceptions emerged. Qualitative data were organised into four themes: client satisfaction, health-seeking behaviour, risk perception and behaviour, and service delivery strengthening. Results: The majority of those interviewed were older (36–65 years old), South African, with secondary education, employed full-time, in stable relationships, and having children. Overall users were satisfied with RWC locations, operating hours, infrastructure, and healthcare worker attitudes. Half of the non-users did not access routine healthcare anywhere. Non-users primarily did not access the RWCs because they did not know the operating times and preferred local facilities. Both groups used traditional healers and pharmacies. RWC users accessed traditional healers and pharmacies for services not available to them at the RWCs. Both groups reported not using private general practitioners or specialists. Both groups provided recommendations for strengthening the service delivery model including an increased focus on non-communicable diseases and occupationally-required health services including vaccinations. Conclusion: Comprehensive care packages delivered through accessible satellite facilities should form the foundation of service delivery models for truck drivers and other mobile populations. Highlights: Satisfaction with locations, operating hours, infrastructure, and healthcare worker attitudes. Truck drivers accessed traditional healers and pharmacies for services not at RWCs. No healthcare sought at private general practitioners or specialists Comprehensive care in satellite facilities should form service delivery models for truck drivers. An increased focus on non-communicable diseases and occupationally-required health services.